Effects of Cooling Fluid Flow Rate on the Critical Heat Flux and Flow Stability in the Plate Fuel Type 2 MW TRIGA Reactor - H. P. Rahardjo; V. I. Sri Wardhani (Atom Indonesia, 2017)
The conversion program of the 2 MW TRIGA reactor in Bandung consisted of the replacement of cylindrical fuel (produced by General Atomic) with plate fuel (produced by BATAN). The replacement led into the change of core cooling process from upward natural convection type to downward forced convection type, and resulted in different thermohydraulic safety criteria, such as critical heat flux (CHF) limit, boiling limit, and cooling fluid flow stability. In this paper, a thermohydraulic safety analysis of the converted TRIGA reactor is presented by considering the Dynamic Nucleate Boiling Ratio (DNBR) criterion, Onset Nucleate Boiling Ratio (ONBR) limit, and cooling fluid flow stability at various cooling fluid flow rate.The numerical analyses were performed using the HEATHYD program on the hottest channels of reactor core.The combination of heat transfer and fluid flow analysis were conducted for reactor operation at 2 MW with 20 fuel element bundles and four control rod bundles. Incoming fluid flow to the cooling channel was fixed at 44.5 °C temperature and 1.9970 bar pressure, and its flow rate was varied from 1.25 to 3.5 m3/h. By inputting these values, as well as the total power of fuel elements per bundle, the wall temperature distribution of the plate fuel element, cooling fluid temperature distribution, and pressure losses in the channels were obtained for the analysis of CHF limit, boiling limit, and flow stability. It was shown that no boiling occurred for the cooling fluid flow rate range of 2.4 to 3.5 m3/h, and even at the cooling fluid flow rate of 1.25 m3/h where some bubbles occurred, the DNBR was higher than the critical limit (more than 23) while the flow stability criterion in some channels were slightly less than 1 (unstable). At the cooling fluid flow rate of 1.4 m3/h, however, the flow became stable in all channel. The results showed that even though some bubbles start to occur, the plate-fuel-   type 2 MW TRIGA reactor can safely operate in the terms of CHF limit and flow stability.